Legal Analysis of Corporate Criminal Liability in Oil and Gas Sector Crimes in Indonesia - Eben Heser Tarigan; Yasmirah Mandasari Saragih (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2024)
This research explores corporate criminal liability in the context of crimes committed within Indonesia's oil and gas sector. In the framework of modern criminal law, corporations are increasingly recognized as legal subjects that can bear criminal responsibility, particularly in cases related to economic crimes, environmental violations, and corruption. Given the oil and gas sector’s strategic significance and high economic value, it is especially vulnerable to legal violations committed by corporate entities. The research adopts a normative juridical method, utilizing statutory, conceptual, and case study approaches to analyze the current state of legal accountability mechanisms. The findings indicate that corporate criminal liability in the oil and gas sector is not explicitly regulated under Indonesia’s Oil and Gas Law, resulting in significant legal gaps that hinder effective enforcement. Although several laws—such as the Anti-Corruption Law, the Environmental Protection and Management Law, and Supreme Court Regulation (PERMA) No. 13 of 2016—provide a basis for prosecuting corporations, their specific application within the oil and gas sector remains limited. This limited application is attributed to several challenges, including technical difficulties in proving corporate guilt, limited investigative capacity and resources among law enforcement authorities, and the disproportionate influence and economic dominance of oil and gas corporations in regulatory and judicial processes. To address these challenges, the research emphasizes the urgent need for reformulating the legal framework governing corporate liability in the oil and gas industry. This includes incorporating explicit corporate criminal liability provisions into sector-specific laws, strengthening institutional enforcement capacity, and applying legal doctrines such as corporate culture theory and strict liability. These efforts aim to ensure that corporations in the oil and gas sector can be held accountable for criminal actions, promote legal certainty, and uphold environmental and economic justice in Indonesia.